ASERCTIVE EXERCISE APPLICATION TO INCREASE EMOTIONAL REGULATION ON VICTIMS OF BULLYING IN SMK PGRI 1 BANYUWANGI : PENERAPAN LATIHAN ASERTIF UNTUK MENINGKATKAN REGULASI EMOSI PADA KORBAN BULLYING DI SMK PGRI 1 BANYUWANGI - Qonita Fauziah; Heriberthus Wicaksono; Ratna Wulandari (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
This research aims to determine the effect of assertiveness training to improve emotional regulation in victims of bullying. The subjects in this research were 7 students who were victims of bullying at school. This research was taken based on the results of identifying victims of bullying as well as the results of the pretest on the bullying behavior scale in the high category and the emotional regulation scale in the low category. The research design used was A-B-A SSR (single subject research) one group pretest and posttest The data collection tools used were a bullying behavior scale to identify bullying victims, an emotional regulation scale, observation and documentation. Researchers used data analysis techniques with the Statistical Program For Social Sciences (SPSS) 2.6 For Windows ll test to obtain a calculated t value of 27,033, meaning that there had been a level of emotional regulation in bullying victims. With df-n-1, d6 is obtained at a significance level of 5%, so the result is t table 1,943, meaning t count > t table (27,033 > 1943). Thus, it can be concluded that the FHA which states Assertive training has an effect on the level of emotional regulation in students who are victims of bullying at SMK PGRI I Banyuwangi is accepted. The results of the research show that assertive training has proven effective in improving emotional regulation in students who are victims of bullying at Vocational School PGRI 1 Banyuwangi.